Plant Mediated Interactions: Lower Sawfly Survival on Pines Previously Browsed by Moose - Nordkvist, Michelle; Björkman, Christer; Klapwijk, Maartje J. (Frontiers in Ecology and Evolution, 2021)
Insect herbivore performance and arthropod communities can be affected by mammalian grazing and browsing via altered plant communities and vegetation structure. Far less is known about whether changes to plant architecture can cause similar effects. Browsing generated changes to within plant architecture could potentially have large consequences for arthropod communities, herbivore survival and eventually damage to plants. This study investigates plant-mediated effects of ungulate browsing on arthropod predator communities and on the survival of herbivorous insects. More specifically we studied how different levels of ungulate browsing 1) influenced the arthropod predator community on Scots pine (Pinus sylvestris) and 2) affected the survival of the European pine sawfly (Neodiprion sertifer). We related these response variables to browsing-inflicted changes in pine architecture. An observational study of generalist arthropod predators on pine trees revealed a trend towards a quadratic response of ants to browsing intensity – i.e. a higher abundance of ants on moderately browsed trees and lower abundance on intensively browsed trees. A field survey of sawfly larvae revealed a 19% lower larval survival on browsed compared to un-browsed pines, but no difference in survival comparing pines with moderate and high intensity of browsing. A structural equation model revealed that moose generated changes to pine architecture had only a small effect on sawfly larval survival, suggesting additional mediating pine traits affected by browsing. We conclude that insect survival can be altered by ungulate browsing, which could affect damage levels.